Interfacial chemistry and structural engineering modified carbon fibers for stable sodium metal anodes - Chenxiao Chu; Chunting Wang; Weisong Meng; Feipeng Cai; Bo Wang; Nana Wang; Jian Yang; Zhongchao Bai (Carbon Energy)
Abstract Sodium (Na) metal stands out as a highly promising anode material for high‐energy‐density Na batteries owing to its abundant resources and exceptional theoretical capacity at low redox potential. Nevertheless, the uncontrolled growth of Na dendrites and the accompanying volumetric changes during the plating/stripping process lead to safety concerns and poor electrochemical performances. This study introduces nitrogen and oxygen co‐doped carbon nanofiber networks wrapped carbon felt (NO‐CNCF), serving as Na deposition skeletons to facilitate a highly reversible Na metal anode. The NO‐CNCF framework with uniformly distributed “sodiophilic” functional groups, nanonetwork protuberances, and cross‐linked network scaffold structure can avoid charge accumulation and facilitate the dendrite‐free Na deposition. Benefiting from these features, the NO‐CNCF@Na symmetrical cells demonstrate notable enhancements in cycling stability, achieving 4000 h cycles at 1 mA cm−2 for 1 mAh cm−2 and 2400 h cycles at 2 mA cm−2 for 2 mAh cm−2 with voltage overpotential of approximately 6 and 10 mV, respectively. Furthermore, the NVP//NO‐CNCF@Na full cells achieve stable cycling performance and favorable rate capability. This investigation offers novel insights into fabricating a “sodiophilic” matrix with a multistage structure toward high‐performance Na metal batteries.